Dental Faculty Members' Pedagogic Beliefs and Curriculum Aims in Problem‐Based Learning: An Exploratory Study. Issue 8 (1st August 2017) - von Bergmann, HsingChi; Walker, Judith; Dalrymple, Kirsten R.; Shuler, Charles F.
Abstract : The aims of this exploratory study were to explore dental faculty members' views and beliefs regarding knowledge, the dental profession, and teaching and learning and to determine how these views related to their problem‐based learning (PBL) instructional practices. Prior to a PBL in dental education conference held in 2011, all attendees were invited to complete a survey focused on their pedagogical beliefs and practices in PBL. Out of a possible 55 participants, 28 responded. Additionally, during the conference, a forum was held in which preliminary survey findings were shared and participants contributed to focus group data collection. The forum results served to validate and bring deeper understanding to the survey findings. The conference participants who joined the forum (N=32) likely included some or many of the anonymous respondents to the survey, along with additional participants interested in dental educators' beliefs. The findings of the survey and follow‐up forum indicated a disconnect between dental educators' reported views of knowledge and their pedagogical practices in a PBL environment. The results suggested that the degree of participants' tolerance of uncertainty in knowledge and the discrepancy between their epistemological and ontological beliefs about PBL pedagogy influenced their pedagogical choices. These findings support the idea that learner‐centered, inquiry‐based pedagogical approaches such as PBL may create dissonance between beliefs about knowledge and pedagogical practice that require the building of a shared understanding of and commitment to curricular goals prior to implementation to ensure success. The methods used in this study can be useful tools for faculty development in PBL programs in dental education.